Kajian Ekologis untuk Mendukung Produktivitas Budidaya Udang Vaname di Desa Lawallu, Kabupaten Barru, Sulawesi Selatan - Alfian; Bambang Widigdo; Sigid Haryadi; Almira Nadia Kusuma; Ardhana Reswari Utami; Adrian Hidayat (Postgraduate, University of Mataram, 2025)
Soppeng Riaja Subdistrict is one of the coastal areas that has long been utilized for shrimp farming. Since 2007, vannamei shrimp (Litopenaeus vannamei) has been the most widely cultivated species. The biggest challenge faced by shrimp farmers in production is disease outbreaks. Diseases in shrimp cause a decline in shrimp quality and even mortality, which ultimately leads to economic losses and impacts the sustainability of shrimp farming operations. This study aims to evaluate the ecological aspects, including water conditions and carrying capacity, based on its ability to accommodate waste from shrimp farming in Lawallu Village, Soppeng Riaja Subdistrict, Barru Regency, South Sulawesi. The research was conducted from August to October 2023 using a quantitative approach. The findings reveal that vannamei shrimp production in Lawallu Village has been declining annually. In 2023, productivity was recorded at 438 tons, significantly below the sustainable pond productivity benchmark of 1008.9 tons per year. Despite the low productivity, the total shrimp farming area in Lawallu Village has reached 88.66 hectares, exceeding its ideal carrying capacity, which is only 44.84 hectares. Water quality analysis showed that ammonia levels in the shrimp pond waters of Lawallu Village have exceeded the quality standards. The adoption of sustainable aquaculture technology, effective water quality management, and proper wastewater management are essential strategies for achieving sustainable productivity.